Methanolic extract of Abrus precatorius promotes breast cancer MDA-MB-231 cell death by inducing cell cycle arrest at G0/G1 and upregulating Bax - Ibrahim, Wan Suriyani Wan (Elsevier, 2019)
Objective: To determine the anti-proliferative activity of Abrus precatorius (A. precatorius) leaf extracts and their effect on cell death. Methods: A. precatorius leaves were extracted successively with hexane, ethyl acetate and methanol by Soxhlet extraction. Aqueous extract was prepared by decoction at 50 . Extracts of A. precatorius leaves were used to treat selected cancer and normal cell lines for 72 h. Furthermore, 3-(4,5-dimethyl thiazol-2-yl) 2,5-diphenyl tetrazolium bromide assay was performed to determine cell viability. Analysis of cell cycle arrest, apoptosis assay and apoptosis protein expressions were determined by flow cytometry. Results: Methanolic extract of A. precatorius leaves showed the lowest IC50 on MDA-MB-231 cells at (26.40依5.40) μg/mL. Flow cytometry analysis revealed that cell arrest occurred at G0/ G1 phase and the apoptosis assay showed the occurrence of early apoptosis at 48 h in MDAMB- 231 cells treated with methanolic extract of A. precatorius leaves. Methanolic extract of A. precatorius leaves induced apoptosis by upregulation of Bax, p53 and caspase-3 and downregulation of Bcl-2. Conclusions: Methanolic extract of A. precatorius leaves promotes MDA-MB-231 cell death by inducing cell cycle arrest and apoptosis possibly via the mitochondrial-related pathway.